Algeria and Transatlantic Relations - Roberts, Jonathan (Researcher on international affairs); Boukaila, Samy; Toperich, Sasha (Book collections on Project MUSE., 2019)
The purpose of this volume is first and foremost to introduce Algeria to a new audience, from its long-ago origins to present day. The goal was to intrigue the audience in the United States to look at the untapped potential for cooperation that Algeria offers in a multitude of sectors. The volume begins with an account of Algeria's history, from its origins, islamization, period under the Ottoman and Roman empires, colonization, independence, through today. It then continues with analysis on Algeria's economy, its energy, agricultural, business, and education sectors, development, and relationship with the United States. This volume will serve as a milestone in the growing of transatlantic cooperation between Algeria and the United States.